2018
DOI: 10.1590/s2175-97902018000317343
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of leading chalcones with high antiparasitic, against Hymenolepis nana, and antioxidant activities

Abstract: The hymenolepiosis by Hymenolepis nana is a major public health problem in developing countries, and the commercial drugs against this parasitosis are not enough effective. The combination of antiparasitic and antioxidant agents has improved the treatment of some parasitoses. Thus, the development of new cestocidal and antioxidant agents to treat the hymenolepiosis cases is important. In the present study, four hydroxy-and four dihydroxy-chalcones were synthesized using the catalyst boron trifluoride diethyl e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Díaz-Carrillo et al found out the number and position of hydroxyl substituent in ring B to be responsible for the chalcone antiparasitic activity of chalcones 105 and 106 which at 20 mg/mL was able to kill the parasite at the lesser treatment time about six times lower than the control drug Praziquantel. In conclusion, at least one meta or para hydroxyl group in ring B was adequate for the activity of the synthetic chalcones against H. nana parasite [27] (Fig. 9).…”
Section: Anthelmintic Activitymentioning
confidence: 81%
See 2 more Smart Citations
“…Díaz-Carrillo et al found out the number and position of hydroxyl substituent in ring B to be responsible for the chalcone antiparasitic activity of chalcones 105 and 106 which at 20 mg/mL was able to kill the parasite at the lesser treatment time about six times lower than the control drug Praziquantel. In conclusion, at least one meta or para hydroxyl group in ring B was adequate for the activity of the synthetic chalcones against H. nana parasite [27] (Fig. 9).…”
Section: Anthelmintic Activitymentioning
confidence: 81%
“…In another investigation, Lahsasni and coworkers, surprisingly found compound 107 (68.58% at C = 2μg/ml) more effective as an antioxidant agent than the ascorbic acid [26]. Meanwhile, the meta-and para-dihydroxy substitution patterns in ring B of chalcones (catechol structure in ring B) 108 were the best combinations for the highest antioxidant activity compared to caffeic acid (positive control) [27].…”
Section: Antioxidant Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…[36,37] Due to their potent capacity to scavenge reactive oxygen species as well as the electrophilic nature of the α,βunsaturated ketone moiety, chalcones have also been used as antioxidant agents. [38][39][40] Therefore, considering the electronic properties of chalcone derivatives such as electron acceptor, it is relevant to investigate the effects of these compounds as electron transport chain inhibitors, blocking electron flow through photosystem II (PS II). In this work, we set out to evaluate chalcone derivatives containing aromatic rings bearing electron donating and withdrawing groups as well as heteroaromatic rings in post-emergent herbicide assays such as photosynthesis and plant growth inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, chalcones can be readily synthetized through a wide array of methodologies, [25] providing easy access to a broad structural diversity, and thus affording a variety of biological activities, [26] as anti‐inflammatory, [27,28] antitumoral, [29] antiviral, [30] insecticide, [31,32] nematicide, [33] larvicide [34,35] and herbicide [36,37] . Due to their potent capacity to scavenge reactive oxygen species as well as the electrophilic nature of the α,β‐unsaturated ketone moiety, chalcones have also been used as antioxidant agents [38–40] . Therefore, considering the electronic properties of chalcone derivatives such as electron acceptor, it is relevant to investigate the effects of these compounds as electron transport chain inhibitors, blocking electron flow through photosystem II (PS II).…”
Section: Introductionmentioning
confidence: 99%